Konseling Cognitive Behavior Therapy Islami untuk Meningkat Self-Regulated Learning Santri Tingkat Mts - Isna Suryaningsih Munawar; Imas Kania Rahman; A. Rahmat Rosyadi (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
In Islamic boarding schools, santri are required to be able to adapt well to the activities and regulations that apply. The number of schedules that must be accepted by santri, sometimes creates different conditions that can have an impact on their life patterns. However, sometimes it is found that some Mts santri have difficulty in the learning process. Therefore, one way to overcome these learning difficulties is to increase self-regulated learning. The Islamic cognitive behavior therapy treatment is one of the effective efforts to increase self-regulated learning for MTs santri which can be observed through changes in the behavior and thoughts of these santri. The purpose of this research is to formulate how Islamic cognitive behavior therapy counseling is effective to improve self-regulated learning for santri at the Mts level. This research uses a quantitative quasi-experimental method and a nonequivalent control group design model through a pre-posttest approach. Based on the results of the research, after Islamic cognitive behavior therapy counseling, there was an increase in the medium category from 11 santri, it decreased to 2 santri and in the high category from 16 santri it increased rapidly to 27 santri. The experimental class has a mean of 90.37 while the control class has a mean of 83.57. Thus, it can be interpreted that the provision of Islamic cognitive behavior therapy to santri increases self-regulated learning. The implementation of the Islamic cognitive behavior therapy approach uses functional analysis of ABC (Antencedent, Behavior, Consequences) which has been modified with Islamic values ​​and invites santri to always be optimistic (at-tafâul) and help (at-ta'awûn) in their learning. Keywords: Counseling, Islamic CBT, Self-Regulated Learning